Prosocial behavior in toddlerhood and early childhood: Consistency across subtypes and over time - Paz, Yael; Davidov, Maayan; Orlitsky, Tal; Hayut, Mor; Roth-Hanania, Ronit; Zahn-Waxler, Carolyn (Frontiers in Psychology, 2023)
Prosocial behavior is considered one of the cornerstones of a harmonious society and a testament to the human potential for compassion. Despite considerable interest in the early roots of prosociality there is limited knowledge regarding the convergence and longitudinal consistency of different subtypes of prosociality, as well as regarding the meaning of young children’s spontaneous versus cued prosocial behavior. The current longitudinal study (N=151) addressed these gaps by examining three prosocial subtypes—instrumental helping, compassionate helping (comforting), and sharing—in toddlerhood (18 months) and early childhood (36 months). Consistent with hypothesis, partial convergence was found between the different prosociality subtypes at each age. Individual differences in prosociality also showed moderate continuity over time, both within and across prosocial subtypes. Moreover, at both ages, when children helped or shared spontaneously, they also provided greater assistance at the task. Children’s tendency to help others spontaneously was partially consistent across situations by early childhood. Taken together, young children show their capacity for compassion and their desire to enhance the welfare of others in multiple ways, which are distinct yet also interrelated and modestly consistent during the early years of life.